Weathering the storm: Children’s resilience against bullying and harassment - Hansen, Karl Tobias (UiT Norges arktiske universitet, 2021)
Resilience is a concept of growing interest in the research field, as well as bullying and quality of life. Resilience has gained rising interest over the past decade because it has capacity for systematically informed prevention and intervention (Elbau et al. 2019). This study looks at data from a former study “Trivsel I Tromsø” with children and adolescence victims to bullying and harassment (N=237) and a control group (N=735). In total (N=952). The pupils that matched the criteria, were from 9 to 16 years, who bullied and/or harassed at the cut off-point 3 or more times a month. The aim of the study was to look for any evidence of resilience within the bullied and harassed group. To assess this The Strenghts and Difficulties Questionnaire (SDQ) were used, and resilience was defined within the children or adolescence who scored in the normal range of total difficulty. Furthermore, KINDLR and the SDQ Pro-social score was used in effort to map out trends of resilience within the dataset. This is followed by regression analyses to sort out which variables had the most resistance towards the negative impacts. Main result of this study shows that 176 (74%) of the pupils were resilient towards the bullying and harassment. A moderate resiliency was considered within the borderline N=35 (14,7%), the last group N=26 (10,9%) were associated with low resilience. Compared to the control group, the most important protective factors were friends, the school environment, and emotional well-being in reducing the negative impacts displayed by the SDQ (with some reservations during overlap issues). The also study notes that physical well-being and self-esteem, and pro-social factors has effects against bullying and suggests that family has an effect in lowering the negative impacts of the bulling and harassment.